Pan-cancer analysis identifies ADAM12 as a prognostic biomarker and indicator of immune infiltration in glioma - Peng Lv; Yanbin Zhang; Wenjie Wu; Xiaobing Jiang; Wei Xiang (Scientific Reports)
Abstract ADAM12, part of the adisintegrin and metalloproteases (ADAMs) family, has been widely reported in recent years to be associated with various malignant tumor behaviors, including migration, invasion, and treatment resistance. However, its role at the pan-cancer level remains insufficiently characterized. In this study, pan-cancer data were utilized to elucidate the expression patterns, prognostic significance, and potential roles of ADAM12 within the tumor immune microenvironment. An in-depth analysis of ADAM12 in gliomas was also conducted. Our findings revealed that ADAM12 expression is markedly overexpressed in glioma tissues, enhances glioma cell malignancy, and is associated with a worse prognosis. These results suggest that ADAM12 may serve as a biomarker for predicting glioma malignancy and patient prognosis, as well as a potential therapeutic target in glioma treatment.